Analysis of the microclimatic behavior of a greenhouse used to produce carnation (Dianthus caryophyllus L.) (2020)
Carnation production in Colombia, the world’s main exporter, takes place entirely in naturally ventilated greenhouses. This type of structure presents non-homogeneous microclimate conditions which differentially affect crop growth and development, which is why this issue has been of great research interest in recent years. The objective was to determine the microclimatic behavior of a passive spatial-type greenhouse used in Colombia for carnation production. The experimental approach included the collection of meteorological data in the external environment through a weather station and in the inside of the greenhouse through a grid of 40 sensors uniformly distributed in a horizontal plane. Data processing to determine the spatial variability of temperature, relative humidity and vapour pressure deficit (VPD) is done by using geostatistical techniques and predicting these variables at unsampled points through the ordinary Kriging method. The main results obtained allowed us to determine that the conditions generated inside the greenhouse are not the optimal ones recommended for carnation production and that, in addition, the behavior of the variables studied shows a heterogeneous distribution, obtaining spatial variations in the horizontal profile evaluated for the night period of 0.5 °C, 9.1% and 1.5 kPa and for the daytime period of 7.2 °C, 42.6% and 1.5 kPa for temperature, humidity and VPD respectively.